The nature of credit markets in developing countries : a framework for policy analysis - Virmani, Arvind; World Bank (Washington, D.C. : World Bank, 1982)
The central purpose of the paper is to analyze various forms of government intervention in the loan market in terms of their effect on efficiency. This provides the essential basis for evaluating and judging these policies. It also shows where earlier policy prescriptions are correct, incomplete or wrong. One of the implications of the paper is that the credit market differs fundamentally from the market for ordinary goods and services. Consequently conventional analysis of the loan markets, based on theory applicable to these goods, can be misleading even when similar prescriptions are reached. This is because the similarity may be restricted to special circumstances. Another important highlight of the paper is the vital role of collateral in the loan market. These two issues are addressed in the introductory discussion on the special nature of credit markets, which forms an important prerequisite for understanding the subsequent section and the rest of the paper.
Includes bibliographical references: p. 154-157.
oo 09/04/2019
Loans
Keywords: Credit; Economic conditions; Developing countries